Traditional Medicinal Plants: A Source of Phytotherapeutic Modality in Resource-Constrained Health Care Settings. (January 2013) - Karunamoorthi, Kaliyaperumal; Jegajeevanram, Kaliyaperumal; Vijayalakshmi, Jegajeevanram; Mengistie, Embialle
Despite recent scientific advancement and globalization, the system of traditional medicine and complementary/alternative medicine is considered as a primary health care modality in the resource-constrained health care settings. Herbal medicinal system has been postulated and established through empirical observation and trial and error experiments since time immemorial to maintain good health and alleviate ailments and diseases. Earlier, the importance of traditional medicinal plants and phytotherapy have often been disregarded and undervalued. Presently revitalization and renewed interest on traditional medicinal plants has been observed among the public and scientific community. However, several daunting challenges need to be flagged effectively and immediately for the promotion of traditional medicinal plants. The collaborative efforts of ethnobotanists, anthropologists, pharmacists, and physicians could be a workable strategy to evaluate and validate the usage of traditional medicinal plants with the modern scientific methods and innovative techniques. Furthermore, conducting clinical trials to assess their efficacy and human safety is imperative and inevitable.